(untitled) (ENTHYMEMA, 2017)
Dans cet article on s’interroge sur le statut d’Une histoire d’amour et de ténèbres, d’Amos Oz, un « roman de la mémoire familiale » dans lequel l’entreprise de remémoration et de reconstitution du passé, victoire sur le silence et les non-dits de l’enfance, est en même temps une façon de s’en débarrasser. This paper interrogates the generic status of Amos Oz’ A Tale of Love and Darkness, a « Family Memoir », in which the task of remembering and reconstructing the past, overcoming the silence and the childhood’s unsaid, is, at the same time, a way to remove it.